EFEKTIFITAS SQUARE STEPPING EXERCISE TERHADAP PENURUNAN RISIKO JATUH PADA LANSIA DI UPT PELAYANAN SOSIAL TRESNA WERDHA (PSTW) BANYUWANGI - Febriawan, Dico M. Gabriel; Dewi, Sofia Rhosma; Suryaningsih, Yeni (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Elderly individuals experience various physiological changes that increase the risk of falls, such as reduced muscle mass, balance, and sensory function. One intervention method that can be used to reduce fall risk is Square Stepping Exercise (SSE), a step-based physical exercise designed to improve balance and coordination in older adults. This study aims to analyze the effectiveness of Square Stepping Exercise in reducing the risk of falls among elderly residents at UPT Pelayanan Sosial Tresna Werdha (PSTW) Banyuwangi. This research employed a pre-experimental design with a one-group pre-test & post-test approach. The study sample consisted of 35 elderly individuals selected using purposive sampling. Data was collected through observations using the Berg Balance Scale (BBS) before and after the SSE intervention. Data analysis was performed using the Wilcoxon Signed Rank Test. The study results showed that the average balance score before the intervention was 28.17, which increased to 38.77 after the intervention. The Wilcoxon test results indicated a p-value of 0.000 (p < 0.05), demonstrating a significant difference in balance scores before and after the intervention. Square Stepping Exercise is proven effective in reducing the risk of falls among the elderly at UPT PSTW Banyuwangi. This exercise can be adopted as a preventive measure to enhance balance in older adults. It is recommended that Square Stepping Exercise be routinely implemented in social care homes and elderly communities as a fall prevention strategy. Healthcare providers can offer education and guidance to ensure that older adults can perform this exercise independently or with supervision.